Africa Flores - Launch Website, English - NASA Marshall Space Flight Center (2019)
Africa Flores, regional coordinator for SERVIR-Amazonia at NASA-Marshall Space Flight Center in Huntsville talks about the Program and invites users to go to the Website https://servir.ciat.cgiar.org/